A clinicoepidemiological study of adult acne among females: Is it surpassing the adolescent acne? - Harish Muddanahalli Rajegowda; B S Suman; Shashi Kumar Basavapura Madegowda; Deepadarshan Kalegowda; Bhagya Shree Shettar Rajendra (Wolters Kluwer Medknow Publications, 2021)
Background: Acne is usually recognized as an adolescent skin disorder, but recently prevalence among adults is increasing. There are not many studies on adult acne in Indian population. Objectives: To study the various clinico-epidemiological factors and assess laboratory investigations for underlying hormonal imbalance in patients with adult acne. Objectives: To study the impact of adult acne on psychological stress and patients quality of life. Materials and Methods: In our prospective observational study, female patients over the age of 25 years presenting with acne in a tertiary care hospital were included. All patients were assessed for hormonal imbalances both clinically and with laboratory investigations. Patients were asked to fill questionnaires to assess stress and impairment in quality of life. Statistical analysis used: Descriptive statistics like percentage ,mean, range were used. Inferential statistics like chi square test was used. The statistical significance was evaluated at 95% confidence level (P<0.05). Results: Out of 150 female patients included in the study, the mean age of the patients was 30.19 years. Persistent acne was observed in 77.3%, while it was late onset in 22.7%, with inflammatory acne (76%) being most common. Most patients showed clinical signs of hyperandrogenism but raised total testosterone levels was seen in only 1.3%. Scarring was observed in a majority of patients (76%), and psychological stress in 46.7% patients. Conclusions: Adult acne is predominant in women which can be of late onset or persistent type, is usually inflammatory with predominant distribution involving cheeks, mandible and chin as compared to adolescent acne. Psychological stress assessment and dermatological quality of life index helps in assessing the severity and providing appropriate treatment.